PEMBELAJARAN KELILING DAN LUAS BANGUN DATAR MENGGUNAKAN METODE MATEMATIKA GASING - Sary, Ryky Mandar; Ristiana, Ristiana (Universitas Papua, 2019)
Mathematics learning is a teaching and learning process that is built by teachers to develop students’s thinking creativity in constructing the procedural knowledge for mathematics. The research aims to determine the increase in students' procedural knowledge of the implementation of Gasing mathematical methods on around and the wide flatness, the subject matter of fourth grade students. This study used quantitative research. The study took a sample of a class of 39 students of SDN Plamongansari 01 Semarang. This type of research uses pre-experiment design with the pretest-posttest one group research design. The data obtained were analyzed statistically using the t-test. The test results show that Ho is rejected at the 5% confidence level, or there is a difference between student scores on pre-test and post-test. It means that the implementation of the mathematical method can improve the procedural knowledge of fourth grade of Elementary School students on the subject matter of circumference and area of planes.